Open pisiform fracture: excision or internal fixation?. (9th January 2013) - Agathangelidis, Filon; Boutsiadis, Achilleas; Ditsios, Konstantinos
Abstract : A 53-year-old man presented with an open fracture of the pisiform after a fall on his left wrist. Treatment of the patient presented a dilemma between excision of the proximal fragment and internal fixation. The patient underwent internal fixation with a 2.5 cortical screw. At 6 months follow-up the fracture appeared fully consolidated with full functional recovery of the wrist.